Limites e possibilidades de uma unidade de ensino potencialmente significativa (UEPS) para o ensino de propriedades físicas de compostos orgânicos. - Vendruscolo, Taciana (2017)
Limits and possibilities of a Potentially Meaningful Learning Unit (PMTU) to teach physical properties of organic compounds. The teaching of chemistry still remains far from the profile suggest by the academics and legal documents in terms of contextualization and the use of diversified teaching strategies, in a way to facilitate the students’ learning. The David Ausubel’s cognitivist and constructivist theory, named Meaningful Learning Theory (MLT), suggest the knowledge acquisition has to consider, as the most important factor in the learning process, what the student already knows, because this previous knowledge will serve as anchor for learning new contents, and also, the disposition to learn. Considering those aspects, MLT was the theoretical support employed to develop the present work, on the assumption that student assign meaning for the content worked. Based on that, the general objective of this work, which is linked to Theoretical-Methodological Fundamentals for the Mathematics and Science Education research line (PPGECM/UPF), was to ide ntified the limits and possibilities that may be pointed by addressing the physical properties, specially the solubility, of organic compounds through a Potentially Meaningful Teaching Unit (PMTU) involving different teaching strategies. The PMTUs are teaching sequences, proposed by Moreira, based on MLT, which can act as a way to stimulate the research classroom-oriented, in other words, the applied research. The strategies selected were experimentation, scientific texts reading and computational simulation. The PMTU, educational product analyzed in this dissertation, was developed with 30 high-school students, on third-grade, from public school of Erechim-RS, during 26 periods. The data collection was provided by qualitative and quantitative approach, using previous knowledge survey of the students, systematicevaluations during all pedagogical intervention, specific questions about the chemical contents and group-work (construction and presentation of seminary), as well as, the teacher records. On the first step of intervention was observed that the students brought some previous knowledge about the content, especially those related to their daily life. In the learning evaluation was possible verify evidence of meaningful learning (ML) through associations carried out by students during groups presentation, however, in the somative evaluation, involving objective questions, the results was unsatisfactory. The students showed difficulty to overcome the macroscopy vison for the phenomena being studied, although the approach has sought a deeper level of reflection. One of the most relevant aspects the PMTU provided was the change of attitude by students and teacher. The first one, by becoming more questioning learners and more participative in classroom, and for the teacher,to provide new paths to her pedagogical practice.